American-Sino OB/GYN/Pediatrics Services (ASOG)- Shanghai, Business Plan 2012-16 - Mathew Valayil, Jacob; Ding, Haohong (2012)
The business plan analyses the current situation of American Sino-Ob/Gyn services (ASOG), the trends of OB/GYN industry and customers’ needs. The results are further narrowed down to frame the mission and vision statements, identify a new strategy, develop and suggest implementing the feasible tactics that will lead the sustainable development.